Lamotrigine drug interactions in combination therapy and the influence of therapeutic drug monitoring on clinical outcomes in paediatric patients. Issue 1 (20th February 2019) - Koristkova, Blanka; Grundmann, Milan; Brozmanova, Hana; Kacirova, Ivana
Abstract: The aim was to study the impact of therapeutic drug monitoring (TDM) on paediatric patients on lamotrigine therapy and the evaluation of possible drug interactions, especially in triple antiepileptic drug combinations. During the period of 2001‐2015, 1308 pre‐dose samples were taken from 430 patients <15 years of age as part of routine TDM. Drug interactions were evaluated using calculation of lamotrigine clearance. Valproic acid decreased lamotrigine clearance by 54% in bitherapy, and by 21% in triple therapy with carbamazepine. Carbamazepine increased lamotrigine clearance by 191% in bitherapy. Levetiracetam and topiramate had no effect. The upper limit of lamotrigine therapeutic range (TR) was exceeded in 2% of cases in monotherapy, and in 6%‐7% of cases in bi‐ or triple therapy. About 61% of plasma levels were found within the TR during 2001‐2005, compared to 75% and 74% during 2006‐2010 and 2011‐2015, respectively. Adverse drug reactions (ADRs) were reported in 22 cases. Higher number of supratherapeutic levels in combination therapy led to a 3‐fold increase in incidence of ADRs. Seizures occurred more often daily and monthly during 2001‐2005 and in patients with three or four antiepileptic drugs in combination. Carbamazepine only partially compensated for the inhibitory effect of valproic acid. Lamotrigine clearance in monotherapy in children is similar to adults, but in polytherapy was found higher susceptibility to induction. A significantly higher number of supratherapeutic lamotrigine levels were found in combinations with valproate. Despite poor correlation with TR, both seizure frequency and ADRs declined after the implementation of TDM.